Econometrics : theory and applications with Eviews - Vogelvang, Ben (Harlow, Pearson Education, 2005)
The author of the book combines econometrics with practice by demonstrating its use with the software package Eviews. A quantitative economic research project is simulated in the case studies. Numerous screen shots of Eviews have been included. The emphasis is on understanding how to select the right method of analysis for a given situation and how to apply the theoretical methods in the right way.
includes bibliographical references and index (357 - 363)
nmn, 22/07/16
Loans
Keywords: Econometrics; Econometric theory; Econometric applications; Eviews